KEEFEKTIFAN LAYANAN BIMBINGAN KELOMPOK UNTUK MENGURANGI PERILAKU BULLYING PADA SISWA SMP NEGERI 2 BUKITTINGGI - Egista Karningsih; Syawaluddin; Oriza Sumantri (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research starts from the existence of a phenomenon that occurs in students who carry out bullying behavior, such as students who like to bully weaker students, students who mock them with rude and dirty words, students who call them bad names and students who often isolate and degrade others. in public towards weaker friends. The aim of this research is to determine the effectiveness of group guidance services in reducing bullying behavior at SMP Negeri 2 Bukittinggi. This research uses quantitative methods with one group pre- test and post test. The sample used by researchers was 8 students consisting of 4 students who were bullies and 4 more students who were exposed to bullying behavior at school. The instrument used in this research was a questionnaire. A questionnaire was developed to measure how much bullying behavior a student has. The data analysis technique uses the Wiloxon rank test. The results obtained in this study were a pretest score with a total score of 328 and a posttest score with a total score of 534, after the measurement scale was given and the results were very effective because the hypothesis was accepted, namely the Wilcoxon test results showed the Aaymp.sig value was 0.012, less than 0, 05 therefore there are differences in pretest and posttest scores in the application of group guidance services in reducing bullying behavior in students at SMP Negeri 2 Bukittinggi. Keywords: Group Guidance, Bullying, Students.